Java across different curricula, courses and countries using a common pool of teaching material - Ivanović, Mirjana; Budimac, Zoran; Mishev, Anastas; Bothe, Klaus; Jurca, Ioan (Vilnius University Institute of Data Science and Digital Technologies, 2013)
Under the auspices of a DAAD funded educational project, a subproject devoted to different aspects of teaching the Java programming language started several years ago. The initial intention of the subproject was to attract members of the subproject to prepare some teaching materials for teaching essentials of the Java programming language. During the last two years, some advanced Java topics have been selected and appropriate teaching materials have been produced. The available pool of common teaching materials can be used in a wide range of university courses in participating countries. In this paper we share some of the results and experiences collected during the subproject that come from intensive use of the prepared teaching materials for a variety of Java topics in different countries and universities.
Keywords: course development, preparation of teaching material, common course, Java programming language